FISH-MAKHANA (EURYALE FEROX SAUSB) INTEGRATION- A CASE STUDY OF SUSTAINABlE AQUAFARMING SYSTEM IN NORTH BIHAR
The paper deals with a technique to synchronize two crops, fish and makhana (Euryale ferox Salisb) in a pond. In such eco-friendly integration both crops are mutually benefited. Decomposed plant parts of makhana crop form organic matter that releases nutrients in the water to enhance plankton population. Organic detritus not only acts as food for bottom dwelling fishes (mrigal and common carp) but also provides a suitable substratum for the growth of zooplankton, insect larvae, nematodes and gastropods. Fishes contribute to the control of makhana pests. Their faecal matter acts as organic manure for makhana crop. Plankton population fluctuated between 1260 u/1 to 4030 u/1 in the control pond and 1630 u/1 to 4722 u/1 in the experimental pond. During the grand growth period of makhana crop(April to July